2019
DOI: 10.3892/mmr.2019.10376
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of potential functional significance of microRNA‑3613‑3p in human umbilical vein endothelial cells affected by heat stress

Abstract: Dysregulation of microRNA-3613-3p (miR-3613-3p) was previously reported in endothelial cells (ECs) during heat stress. The aim of the present study was to investigate the precise role of miR-3613-3p in heat stress. In the present study, potential gene targets of miR-3613-3p in heat-treated ECs were assessed, and the potential effects of miR-3613-3p were determined using Gene Ontology enrichment analysis. Kyoto Encyclopedia of Genes and Genomes pathway analysis was used to identify signaling pathways that may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Our previous miRNA expression profiling data in HUVECs indicated that miR-3613-3p may be a HS-related miRNA ( 12 ). Furthermore, using an in vivo approach, our previous study revealed a regulatory relationship between miR-3613-3p and MAP3K2 that mediated the apoptosis of HS-treated HUVECs ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous miRNA expression profiling data in HUVECs indicated that miR-3613-3p may be a HS-related miRNA ( 12 ). Furthermore, using an in vivo approach, our previous study revealed a regulatory relationship between miR-3613-3p and MAP3K2 that mediated the apoptosis of HS-treated HUVECs ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction and western blot analysis. Protein extraction, measurement of total protein concentration and western blot analysis were performed as described previously (19). The primary antibodies used were as follows: Mouse anti-human MAP3K2 (cat.…”
Section: Rna Extraction and Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
See 1 more Smart Citation